THE WHITE-BELLIED PLANTHOPPER (HEMIPTERA: DELPHACIDAE) INFESTING CORN PLANTS IN SOUTH LAMPUNG, INDONESIA - Susilo, Franciscus Xaverius; Swibawa, I Gede; ., Indriyati; Hariri, Agus Muhammad; ., Purnomo; Hasibuan, Rosma; Wibowo, Lestari; Suharjo, Radix; Fitriana, Yuyun; Dirmawati, Suskandini Ratih; ., Solikhin; ., Sumardiyono; Rwandini, Ruruh Anjar; Sembodo, Dad Resiworo; ., Suputa (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2017)
The White-Bellied Planthopper (Hemiptera: Delphacidae) Infesting Corn Plants in South Lampung, Indonesia. Corn plants in South Lampung were infested by newly-found delphacid planthoppers. The planthopper specimens were collected from heavily-infested corn fields in Natar area, South Lampung. We identified the specimens as the white-bellied planthopper Stenocranus pacificus Kirkaldy (Hemiptera: Delphacidae), and reported their field population abundance.